How water and agriculture support livelihoods in the Volta - Cook, Simon E. (2009)
The CPWF Volta Basin Focal Project project team was led by Institut de Recherche pour le Développement (IRD, France) with collaborating scientists from the International Water Management Institute (IWMI) - Ghana, CSIR Water Research Institute - Ghana, Université de Ouagadougou, Institute of Statistical, Social and Economic Research-Ghana, Institut de Recherches en Sciences de la Santé (IRSS)- Ouagadougou, Institut National des Sciences de la Société (INSS) - Ouagadougou, WorldFish Centre - Egypt, and International Centre for Tropical Agriculture (CIAT).